BAJU BATIK SEBAGAI OMIYAGE : STUDI KASUS PADA MAHASISWA JEPANG YANG PERNAH BELAJAR DI UGM TAHUN 2009-2017 - Mery Kharismawati; Wahyu Handayani; Devi Wardhani; Febri Sahrullah (IZUMI, 2017)
(Title: Batik Clothes As Omiyage: Case Study On Japanese University Students Who Had Studied At UGM In 2009-2017) Batik has long been known as a typical culture of Yogyakarta, and therefore it is most likely chosen by the tourists to take home as souvenir. Until 2017 UGM which is located in Yogyakarta is often visited by students from Japan. As well as studying, they also become tourists who will buy omiyage before returning to Japan. The culture of giving omiyage has existed in Japan since ancient times and until now the term omiyage is still being used for something given to others after traveling. This study aims to determine the relevance of batik clothing as omiyage according to the view of Japanese students who have studied at UGM from 2009-2017. Data were obtained through questionnaire distributed during July 2017 to 60 Japanese students who had studied at UGM. The results of this study indicate that food is still preferred to be omiyage, and batik clothes is not a suitable item to be brought home as omiyage, because of some perceptions about batik clothes as somehing not quite universal to wear in Japan.